Establishment of the South-Eastern Norway Regional Health Authority Resource Center for Children with Prenatal Alcohol/Drug Exposure - Gro C. C. Løhaugen; Marianne Møretrø Flak; Thorsten Gerstner; Cato Sundberg; Bjørn Lerdal; Jon Skranes (SAGE Publishing, 2015)
This paper presents a new initiative in the South-Eastern Health Region of Norway to establish a regional resource center focusing on services for children and adolescents aged 2-18 years with prenatal exposure to alcohol or other drugs. In Norway, the prevalence of fetal alcohol spectrum (FAS) is not known but has been estimated to be between 1 and 2 children per 1000 births, while the prevalence of prenatal exposure to illicit drugs is unknown. The resource center is the first of its kind in Scandinavia and will have three main objectives: (1) provide hospital staff, community health and child welfare personnel, and special educators with information, educational courses, and seminars focused on the identification, diagnosis, and treatment of children with a history of prenatal alcohol/drug exposure; (2) provide specialized health services, such as diagnostic services and intervention planning, for children referred from hospitals in the South-Eastern Health Region of Norway; and (3) initiate multicenter studies focusing on the diagnostic process and evaluation of interventions.